DAYA DUKUNG TANAMAN SAWIT DAN HASIL IKUTAN LIMBAH PENGOLAHAN SAWIT SEBAGAI PAKAN TERNAK SAPI POTONG DI SUMATERA BARAT - Ida Indrayani; James Hellyward; Yozil Alveni (Udayana University, 2016)
This study was to determine the carrying capacity of palm oil plantation and oil palm industry waste could be used as beef cattle feed in West Sumatra. This study used a desk study method, it was the activity that searched secondary data such as the results of other relevant studies, official documents and other important records in several government agencies and other relevant institutions. The analysis showed people carrying capacity of palm oil plantations folk in West Sumatra with the utilization of forage, leaves no stick and palm frond as cattle feed as a whole can accommodate about 390 913 head of cattle. While carrying capacity of byproduct of palm oil processing wastes amounted to 465 812 head of cattle. Overall, therefore, the palm oil plantation folk, the state and the private sector is able to provide beef cattle feed to 856 725 head of cattle. It concluded that beef cattle still have a chancethe to be developed by use oil palm plantation and byproducts as a substitute for forages.Key words: oil palm plantation, carrying capacity, oil palm industry waste, beef cattle feed